Soil Acidity Soil Acidity Mapping of A Swampland Planted with Rice in Ampukung Village, Kelua District, Tabalong Regency - Noor Khamidah; Riza Adrianoor Saputra (TROPICAL WETLAND JOURNAL, 2020)
Tidal swamp land is one type of wetland in South Kalimantan, where the water level is influenced by the season/rainfall. Based on the puddle level and duration, tidal swamp land has three typologies, namely shallow tidal swamp, middle tidal swamp, and deep tidal swamp. The wetlands in Ampukung village are classified in tidal swamps. Most of the tidal swamps have been utilized for agricultural activities, especially rice. Till now, rice farming in the tidal swamps of Ampukung village has not experienced any significant problems. In 2016, the rice harvest in Ampukung village exceeded the target of South Kalimantan. This success is considered to be increased by planting twice a year. However, some issues need to be addressed regarding the characteristics of the land in Ampukung village. Soil fertility, especially soil acidity, is one of the limiting factors in the utilization of tidal swamp land. Therefore, it is necessary to identify the acidity of the soil in the tidal swamp of Ampukung village. The acidity data is basic information to determine the condition of soil fertility to achieve the target of planting rice twice a year. This information will be presented in the form of a map to assist users in interpreting the research data. This study found that the soil pH in the tidal swamp lands of Ampukung Village, which was planted with rice, was highly acidic and homogeneously distributed.